Морфофункциональное состояние бета- и амилинсинтезирующих клеток панкреатических островков в динамике развития стрептозотоцин-индуцированного сахарного диабета у экспериментальных животных - Грекова, Т. А.; Грекова, Тетяна Анатоліївна; Hrekova, T. A. (My University, 2015)
Высокий уровень распространенности сахарного диабета в мире диктует необходимость всестороннего изучения сложной регуляции секреторной активности эндокриноцитов поджелудочной железы. С целью изучения морфофункционального остояния бета- и амилинсинтезирующих клеток панкреатических островков в динамике развития сахарного диабета, протекающего по типу 1, самцам крыс линии Wistar индуцировали экспериментальный сахарный диабет стрептозотоцином. Обнаруженные изменения морфофункциональных параметров панкреатических островков, а также бета- и амилинсинтезирующих клеток при экспериментальном сахарном диабете отражают включение компенсаторных механизмов, направленных на нормализацию концентрации глюкозы крови. Однако в условиях массовой деструкции бета-клеток адаптационные возможности инсулярного аппарата крайне ограничены, вследствие чего не достигается нормогликемическое состояние. Високий рівень поширеності цукрового діабету у всьому світі диктує необхідність всебічного вивчення складної регуляції секреторної активності ендокриноцитів підшлункової залози. Із метою вивчення морфофункціонального стану бета- і амілінсинтезуючих клітин панкреатичних острівців у динаміці розвитку цукрового діабету, що перебігає по типу 1, самцям щурів лінії Wistar було індуковано експериментальний цукровий діабет стрептозотоцином. Виявлені зміни морфофункціональних параметрів панкреатичних острівців, а також бета- і амілінсинтезуючих клітин при експериментальному цукровому діабеті відображають включення компенсаторних механізмів, спрямованих на нормалізацію концентрації глюкози крові. Однак в умовах масової деструкції бета-клітин адаптаційні можливості інсулярного апарату вкрай обмежені, внаслідок чого не досягається нормоглікемічний стан. To study morphological and functional state of pancreatic islets' beta - and amylin synthesize cells in the dynamics of Type 1 diabetes development, male Wistar rats were induced experimental diabetes (EDM) by streptozotocin. Serial sections from different parts of the pancreas thickness of 5 microns were prepared on a microtome MICROM HR-360 (Microm, Germany). To identify beta- and amylin synthesize cells immunofluorescence detection kits of insulin and amylin (produced by Peninsula Laboratories Inc., USA) were used. Identification of pancreatic islets was performed using a computer analysis of a digital image VIDAS-386 (Kontron Elektronik, Germany) in the ultraviolet spectrum under Axioskop microscope with fluorescence attachment (Zeiss, Germany). The resulting image was input by 8-bit CCD-camera COHU-4922 (COHU Inc., USA) in a computer system, digital image analysis VIDAS-386 (Kontron Elektronik, Germany). For each pancreatic islet morphometric parameters (pancreatic islet area, mcm2; area of immunoreactive material in the island, mcm2; area and the number of beta - and amylin synthesize cells in islet) and parameters characterizing the concentration of hormones and their content in the island were studied. Glycemia was measured by "SUPER GLUCOCARD-II" (Arkray Factory, Japan). Statistically significant differences between the results of studies with p <0,05 were established by ANOVA. In rats with EDM hyperglycemia reached 11,36 ± 0,29 mmol/l to the end of the 3rd week, and at the end of the 5th week - 15,76 ± 0,51 mmol/l. The control group animals' blood glucose concentration was in the normal range. All found islets by mathematical classification analysis were divided into types by area: 1) small islands - 100-1500 mcm2; 2) medium - 1500-3500 mcm2; 3) large - 3500-7500 mcm2; 4) huge - more than 7500 mcm2. In animals with a 3-week EDM dominated small islands with low percentages of other types. This trend continued on the 5th week of the EDM. Within 3 weeks occurred islet area reduction of 21% (p <0.05) in EDM animals compared with the control, and the end of the EDM 5th week - of 33% (p <0.05), relatively with a 3-week EDM, which was 47% (p <0,05) decreasing in comparison with the control. According to our data, area islands' reduction up to the end of the 3rd week of EDM was due to decreasing of the beta cells number by 43% (p <0.05), although 33% (p <0,05) growth of their area, in comparison with control animals. Islets' area decreased up to the end of the 5th week of EDM by the 60% (p <0,05) reducing the beta cells' number, but their area was 17% higher (p <0,05) than in control. The concentration of insulin in the beta cells of intact and experimental animals were not significantly changed, but its content in the islets was significantly reduced by 64% and 70% (p <0,05) after 3 and 5 weeks of EDM, relatively of those in the control. The amylin synthesize cells number in islets of animals with 3- and 5-week EDM was significantly lower at 62% and 69% (p <0.05), respectively, compared with the control. Their average area decreased up to the end of the 3rd week of EDM by 11% (p <0.05) and by the end of the 5th week has not significantly changed. The content of amylin in amylin synthesize cells cells did not undergo significant change up to the end of the 3rd week of EDM, and after the 5th week of EDM this parameter increased by 36% (p <0.05) compared with 3-week EDM and control animals. Amylin content in the islets were not significantly altered either at the end of EDM 3rd or 5th week, compared with the control. Conclusions: The development of EDM in rats is accompanied by morphological and functional parameters changes of pancreatic, beta- and amylin synthesize cells. The morphological and functional state of beta and amylin synthesize cells in EDM reflects the inclusion of compensatory mechanisms aimed to normalize blood glucose level: the predominance of small islands, the high activity of insulin secretion, increasing the amylin content in the cells synthesizing it. In terms of massive destruction of beta cells in the EDM the insular apparatus adaptive capacity is extre
Морфофункціональний стан бета- та амілінсинтезуючих клітин панкреатичних острівців в динаміці розвитку стрептозотоцин-індукованого цукрового діабету у кспериментальних тварин
Morphologocal and functional state of pancreatic islets' beta and amylin synthetic cells in the streptozotocininduced diabetes dynamics
Keywords: сахарный диабет; бета-клетки; амилинсинтезирующие клетки; гипергликемия; цукровий діабет; бета-клітини; клітини, що синтезують амілін; гіперглікемія; diabetes; beta-cells; amylin synthetic cells; hyperglycemia